Ultrasonic Behaviour of CoFe2O4·H2O Magnetic Nanofluids for Magnetic Hyperthermia Applications - Ammani Ammal, V. Beula Shanthi; Jebarathinam, N. John; Jayalakshmi, D. (Asian Journal of Chemistry, 2017)
Cobalt ferrite nanoparticles are prepared by low temperature hydrothermal synthesis using EDTA as template. IR, XRD and FESEM analysis indicate formation of single spinel phase cobalt ferrite particles having average particle size of 26 nm. VSM analysis of cobalt ferrite show hysteresis loop with a moderate coercivity of 580 Oe and saturation magnetization of 60 emu/g. Hyperthermia analysis under various AC magnetic field were carried out for magnetic nanofluids prepared by dispersing various amounts of the synthesized cobalt ferrite nanoparticle in water. The specific absorption rate (SAR) values are found to be comparatively higher for magnetic nanofluids containing cobalt ferrite up to 0.6 wt. % and hence the optimum saturation temperature of 43 °C required for the hyperthermia treatment of cancer cells is achieved by the application of lower magnetic field. Ultrasonic investigation on the prepared nanofluids show no particle-particle interaction up to the concentration of 0.6 wt. % and beyond which agglomeration of particles occur results in the formation of small clusters in the magnetic nanofluids. Presence of clusters reduces SAR values and higher magnetic field is required to attain the optimum saturation temperature of 43 °C.